Jati-Shell Sdn. Bhd. / Abdul Hadi Jamaluddin... [et al.] - Jamaluddin, Abdul Hadi; Sahar, Mohd Azmin; Idrus, Sarusirawana; Mohd Shah, Nurul Syamsiah; Norman, Nornadia Elvira (2000)
Jati-Shell Sdn. Bhd operates a petrol pump station under the Shell Licensed. This pump station will be located on the main road at Padang Besar Utara. This company will be retailing gasoline and diesel and will also engage in other complimentary services that will help us maximize profits. There is hardly anyone who doesn’t have a need for gas, this is why it is really vital that one keys into this industry.